Analysis of Campus Performance Measurement of Indonesian College of Economics Using Balanced Scorecard - Aden Apandi; Lies Zulfiati; Nursanita Nursanita (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
Abstract— This study aims to determine the performance of the Indonesia College of Economics (STEI) with balanced scorecard in a financial perspective, customer perspective, internal business process perspective and learning and development perspective.This research method is quantitative descriptive method. The object of this research is the STEI campus, with the sample selected using the purposive sampling method, namely by determining that the sample is the party that can provide information about the desired data. The sample of this study consists of the financial section for secondary data in the form of 2017 and 2018 financial statements for the financial perspective, while for the customer perspective is students, the sample for internal business process perspective is STEI's permanent and non-permanent lecturers and the learning and growth perspective is STEI's employees . This data analysis technique is common size and uses descriptive statistical methods, namely the validity and reliability tests used to test the research questionnaire.The results of this study indicate that the performance of STEI in a financial perspective is good because it has reached the target set, from the perspective of the customer that the performance of STEI is said to be good, this is seen from the average value of statement items on the customer's perspective that shows the answers of student respondents tend to agree with the answers and have a good interpretation. While from the perspective of internal business processes STEI performance is said to be good, this can be seen from the average value of the question items on the perspective of internal business processes which show respondents' answers tend to be answers agree and have good interpretations. As well as the learning perspective and the development of a good STEI performance, this can also be seen from the average value of the question items on the learning and growth perspective which shows the respondents' answers tend to be the answers agree with and have good interpretations.